Pengaruh Budaya Keamanan Siber terhadap Kinerja Karyawan dalam Sistem Transportasi Publik Digital: Studi Kasus Suroboyo Bus - Agoes Hadi Poernomo (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The digital transformation of public transport services requires organizations not only to develop technology but also to build a strong cybersecurity culture. This article analyzes the impact of cybersecurity culture on employee performance with digital literacy as a moderating variable using Suroboyo Bus as a case study. Data were collected via a quantitative survey of 124 respondents, selected through simple random sampling from 180 active employees involved in digital operations. Cybersecurity culture was measured across four dimensions: security awareness, policy compliance, security behavior, and management support and training. Analysis was conducted using Moderated Regression Analysis (MRA). The results indicate that security awareness (X1), cybersecurity behavior (X3), and management support and security training (X4) have a positive and significant impact on performance. Conversely, security policy compliance (X2) did not have a significant effect, as compliance was largely administrative in nature and had not yet been internalized as a work behavior. Moderation testing revealed that digital literacy (M) strengthens the impact of security awareness (X1) on performance but does not moderate the relationship between cybersecurity behavior (X3) and performance. The novelty of this study lies in the integration of cybersecurity culture and digital literacy within the context of digital public transport in Indonesia a topic rarely examined empirically. These findings offer practical contributions for public sector management in designing behavior-based cybersecurity policies and enhancing employee digital literacy to support operational performance.